This equation can be used when comparing ages.
An example to illustrate this:
Assume that adding 6 to 3 times the age of Jack will give us the age of his grandfather.
When translating this into equations, assuming that the age of jack is "a" and the age of his grandfather is "b", we will find that:
b = 6 + 3a
Answer:
Step-by-step explanation:
Maybe 8 feet
Answer:
The answer would be positive 6
Step-by-step explanation:
I know it is -6 because when you solve this you do...
-x = -6
Divide both sides by -6
-x/-6 = -6/-6
the answer would be 6
because a negative divided by a negative is a positive.
Hope this helps have a great day! :)
Answer:
![T_n=-1(-5)^n^-^1](https://tex.z-dn.net/?f=T_n%3D-1%28-5%29%5En%5E-%5E1)
Step-by-step explanation:
We are given;
A geometric sequence;
-2,10,-50
Required to determine the nth term
The nth term in a geometric sequence is given by the formula;
![T_n=a_1r^n^-^1](https://tex.z-dn.net/?f=T_n%3Da_1r%5En%5E-%5E1)
where
is the first term and r is the common ratio;
In this case;
![a_1=-2](https://tex.z-dn.net/?f=a_1%3D-2)
r = 10 ÷ -2
= -5
Therefore;
To get the nth term in the given geometric sequence we use;
![T_n=-1(-5)^n^-^1](https://tex.z-dn.net/?f=T_n%3D-1%28-5%29%5En%5E-%5E1)
Thus, the nth term is ![T_n=-1(-5)^n^-^1](https://tex.z-dn.net/?f=T_n%3D-1%28-5%29%5En%5E-%5E1)